Rainbows in Pixels: LGBTQ Representation on Animated Content in YouTube Kids - Gissena, Annisa (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2025)
This study examines the representation of LGBTQ themes in children’s animated content on YouTube Kids, a widely accessed platform among children. In Indonesia, such content is controversial due to conflicting social norms. Using representation theory and qualitative content analysis, six animated videos were analyzed through visuals, dialogue, and narrative elements. The findings reveal both explicit and implicit portrayals of LGBTQ identities, including lesbian, gay, transgender, and queer, through human and anthropomorphic characters. These themes appear in various formats such as children’s series, music, and storytelling videos, often subtly embedded within broader narratives. The study concludes that while LGBTQ representation is generally subtle, it significantly contributes to shaping children's understanding of gender identity and sexuality. The research highlights the importance of balancing global inclusivity with sensitivity to local cultural values in media policy.